Entrepreneurial Climate – Management of Women’s Entrepreneurship - Vidovic, Aleksandra (International Journal of Engineering and Management Sciences, 2024)
Entrepreneurship, which people can have without formal economic education, is a tendency acquired through upbringing in the family, competition in school, implies risk and constant self-affirmation through the acquisition of profits and losses, so that it represents the sum of successes and failures, victory and defeat. In the last thirty years, female entrepreneurship has been developing more and more, especially in less developed countries, the reason for such growth is primarily reflected in the promotion of equality between men and women, the right to education, and the development of democracy. Female entrepreneurship is a significant factor in economic development, so the national economy becomes richer. The subject of this research are the entrepreneurial climate in the Balkans compared to the world in terms of female entrepreneurship, what is the role of the family in starting a small business, as well as its survival and growth. In the study the results of previous research in this area. The research method is based on a comparative analysis of studies dealing with this problem from the territory of Balkans. It can be concluded that in the Balkans, female entrepreneurship is still in its infancy, it is about a very small percentage of female entrepreneurs, although according to research, it is evident that there has been no major progress in the last 15 years. Recommendation In the countries of the Balkans, there is a good entrepreneurial climate for the development of female entrepreneurship, especially because women can work from home, and in the future it is necessary to go in this direction.